Promiscuous Chemokine Antagonist (BKT130) Suppresses Laser-Induced Choroidal Neovascularization by Inhibition of Monocyte Recruitment - Hagbi-Levi, Shira (J Immunol Res, 2019)
BACKGROUND: Age-related macular degeneration (AMD), the most common cause of blindness in the developed world, usually affects individuals older than 60 years of age. The majority of visual loss in this disease is attributable to the development of choroidal neovascularization (CNV). Mononuclear phagocytes, including monocytes and their tissue descendants, macrophages, have long been implicated in the pathogenesis of neovascular AMD (nvAMD). Current therapies for nvAMD are based on targeting vascular endothelial growth factor (VEGF). This study is aimed at assessing if perturbation of chemokine signaling and mononuclear cell recruitment may serve as novel complementary therapeutic targets for nvAMD. METHODS: A promiscuous chemokine antagonist (BKT130), aflibercept treatment, or combined BKT130+aflibercept treatment was tested in an in vivo laser-induced model of choroidal neovascularization (LI-CNV) and in an ex vivo choroidal sprouting assay (CSA). Quantification of CD11b+ cell in the CNV area was performed, and mRNA levels of genes implicated in CNV growth were measured in the retina and RPE-choroid. RESULTS: BKT130 reduced the CNV area and recruitment of CD11b+ cells by 30-35%. No effect of BKT130 on macrophages' proangiogenic phenotype was demonstrated ex vivo, but a lower VEGFA and CCR2 expression was found in the RPE-choroid and a lower expression of TNFα and NOS1 was found in both RPE-choroid and retinal tissues in the LI-CNV model under treatment with BKT130. CONCLUSIONS: Targeting monocyte recruitment via perturbation of chemokine signaling can reduce the size of experimental CNV and should be evaluated as a potential novel therapeutic modality for nvAMD.